1986
DOI: 10.1111/j.1365-2591.1986.tb00491.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of irrigants in removing root canal debris when used with an ultrasonic preparation technique

Abstract: Three types of irrigant, 2.6 per cent sodium hypochlorite, water and Solvidont were compared for their ability to remove debris during root canal preparation with ultrasonically operated K files. Twenty-seven freshly extracted human teeth were divided into three groups, and each group prepared using one of the irrigants. The teeth were sectioned longitudinally, stained and photographed for assessment by a ranking system. Canals prepared with sodium hypochlorite were found to have significantly less debris rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

1988
1988
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 16 publications
1
14
0
2
Order By: Relevance
“…This regular repeating pattern has been noticed by other investigators when assessing the cleanliness 84 of canals prepared by ultrasonics (4,5) but are not a feature of those canals which have been prepared with sonic instruments (6,7). When these instruments are used then the markings consist of either regular bands (6) or longitudinal parallel grooves (7).…”
supporting
confidence: 70%
“…This regular repeating pattern has been noticed by other investigators when assessing the cleanliness 84 of canals prepared by ultrasonics (4,5) but are not a feature of those canals which have been prepared with sonic instruments (6,7). When these instruments are used then the markings consist of either regular bands (6) or longitudinal parallel grooves (7).…”
supporting
confidence: 70%
“…A continuous flow of NaOCl activated by an ultrasonic delivery system was used for the preparation and irrigation of canals. Smear‐free canal surfaces were observed using this method (Cameron 1983, 1987a,b, Griffiths & Stock 1986, Alaçam 1987). Whilst concentrations of 2–4% sodium hypochlorite in combination with ultrasonic energy were able to remove smear layer, lower concentrations of the solutions were unsatisfactory (Cameron 1988).…”
Section: Methods To Remove the Smear Layermentioning
confidence: 99%
“…US is a useful adjunct in cleaning these difficult anatomical features. It has been demonstrated that an irrigant in conjunction with ultrasonic vibration, which generates a continuous movement of the irrigant, is directly associated with the effectiveness of the cleaning of the root canal space (22,(137)(138)(139)(140)(141)(142).…”
Section: Increased Action Of Irrigating Solutionsmentioning
confidence: 99%